2014
DOI: 10.1007/s00345-014-1398-y
|View full text |Cite
|
Sign up to set email alerts
|

Are lower urinary tract symptoms associated with cardiovascular disease in the Dutch general population? Results from the Krimpen study

Abstract: The cross-sectional analyses revealed a clear correlation between moderate to severe LUTS and CVD. In longitudinal analyses, however, no significant association was shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…LUTS is perhaps undercoded because it is a symptom diagnosis. Thus, this error might underestimate the effect of LUTS on subsequent PAOD [24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LUTS is perhaps undercoded because it is a symptom diagnosis. Thus, this error might underestimate the effect of LUTS on subsequent PAOD [24]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the use of ICD-CM-9 codes for diagnosing chronic diseases has been validated in previous national cohort studies [10, 24, 3335]. The NHIRD covers a highly representative sample of Taiwan’s general population because the reimbursement policy is universal and operated by a single-buyer, the government in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…The Boston Area Community Health Survey and Third National Health and Nutrition Examination Survey showed the relationship between LUTS and metabolic syndrome . In addition, several studies have shown that LUTS is associated with an increase in the prevalence of cardiovascular events, although there were differences in the methodology used for statistical analysis in these studies . In contrast, Bouwman et al .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In addition, several studies have shown that LUTS is associated with an increase in the prevalence of cardiovascular events, although there were differences in the methodology used for statistical analysis in these studies. [27][28][29][30][31][32][33][34][35][36] In contrast, Bouwman et al reported that LUTS is not an independent predictor of cardiovascular events in men without a history of CVD, whereas an association between LUTS and cardiovascular events has been shown by cross-sectional studies. 37 It remains unclear whether LUTS/BPH is an independent predictor of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
“…Taken into account these premises, it should be noted that all previous pathogenetic mechanisms are known to increase cardiovascular disease (CVD) risk [12].…”
mentioning
confidence: 99%